(untitled) (Canadian Medical Education Journal, 2025)
Background: As institutions strive to incorporate Equity, Diversity, Inclusion, Indigeneity, and Accessibility (EDIIA) principles into their policies and curricula, various forms of discrimination persist within the medical education system. The objective of this study was to understand learner experiences related to racism, discrimination and microaggressions in a large Canadian medical school to ultimately inform future efforts to address issues identified. Methods: This survey-based study was distributed to all current medical students and residents at a large Canadian University. Questions focused on lived and witnessed experiences of microaggressions, discrimination or racism during medical education. We computed descriptive statistics and risk ratios for experienced or witnessed events. Results: The survey response rate was 12.4% (321/2579), with 26% of participants self-identifying as Black, Indigenous or People of Color (BIPOC). During medical education, 30% of respondents reported experiencing racism or microaggressions, while 51% reported witnessing these events. Attending physicians (31%) and patients/families (22%) were most likely to be identified as responsible. Common proposed solutions by respondents included: Anonymous reporting systems, dedicated counsellors from BIPOC groups, education of healthcare professionals on microaggressions and discrimination and increased peer/faculty support. Conclusions: Among participants, this study described a high rate of witnessed or experienced racism or microaggressions during medical education, leading to local interventions to improve the psychological safety of learners.